Targeting the Sugary Armor of Klebsiella Species - Patro, L. Ponoop Prasad; Rathinavelan, Thenmalarchelvi (Frontiers in Cellular and Infection Microbiology, 2019)
The emergence of multidrug-resistant strains of Gram-negative Klebsiella species is an urgent global threat. The World Health Organization has listed Klebsiella pneumoniae as one of the global priority pathogens in critical need of next-generation antibiotics. Compared to other Gram-negative pathogens, K. pneumoniae accumulates a greater diversity of antimicrobial-resistant genes at a higher frequency. The evolution of a hypervirulent phenotype of K. pneumoniae is yet another concern. It has a broad ecological distribution affecting humans, agricultural animals, plants, and aquatic animals. Extracellular polysaccharides of Klebsiella, such as lipopolysaccharides, capsular polysaccharides, and exopolysaccharides, play crucial roles in conferring resistance against the host immune response, as well as in colonization, surface adhesion, and for protection against antibiotics and bacteriophages. These extracellular polysaccharides are major virulent determinants and are highly divergent with respect to their antigenic properties. Wzx/Wzy-, ABC-, and synthase-dependent proteinaceous nano-machineries are involved in the biosynthesis, transport, and cell surface expression of these sugar molecules. Although the proteins involved in the biosynthesis and surface expression of these sugar molecules represent potential drug targets, variation in the amino acid sequences of some of these proteins, in combination with diversity in their sugar composition, poses a major challenge to the design of a universal drug for Klebsiella infections. This review discusses the challenges in universal Klebsiella vaccine and drug development from the perspective of antigen sugar compositions and the proteins involved in extracellular antigen transport.